3
$\begingroup$

Exercise 7 in Rose's A Course On Group Theory reads

Let $g\in G$ with $o(g) = n_1n_2$, where $n_1$ and $n_2$ are co-prime positive integers. Then there are elements $g_1, g_2 \in G$ such that $g = g_1g_2 = g_2g_1$ and $o(g_1) = n_1$, $o(g_2) = n_2$. Moreover, $g_1$ and $g_2$ are uniquely determined by these conditions.

I proved the first part easily enough: since $n_1$ and $n_2$ are co-prime, there exist integers $s_1$ and $s_2$ such that $n_1 s_1 + n_2 s_2 = 1$. Letting $g_1 = g^{n_2 s_2}$, $g_2 = g^{n_1 s_1}$ does the trick; one does need to know the formula $o(g^m) = o(g)/\gcd(o(g), m)$ and note that $\gcd(n_1,s_2) = \gcd(n_2, s_1) = 1$.

I'm stuck on the bolded part. If I assume $g = xy$ with $xy = yx$ and $o(x) = n_1$ and $o(y) = n_2$, how do I get $x = g_1$ and $y = g_2$?

$\endgroup$
5
$\begingroup$

Oh, I got it. Since $n_2s_2 = 1 - n_1s_1$ and since $x = gy^{-1} = y^{-1}g$, $$x = x^{1 - n_1s_1} = x^{n_2s_2} = g^{n_2 s_2}(y^{n_2})^{-s_2} = g_1.$$ Use the exponent $1 - n_2s_2$ for $y$!

$\endgroup$
1
  • 1
    $\begingroup$ Thanks! Upvoting is easier than writing out a proof! $\endgroup$ – André Nicolas Jun 4 '15 at 17:14

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.